Functional Amyloids and their Possible Influence on Alzheimer Disease - Lau, Angus (Discoveries (Craiova), 2017)
Amyloids play critical roles in human diseases but have increasingly been recognized to also exist naturally. Shared physicochemical characteristics of amyloids and of their smaller oligomeric building blocks offer the prospect of molecular interactions and crosstalk amongst these assemblies, including the propensity to mutually influence aggregation. A case in point might be the recent discovery of an interaction between the amyloid β peptide (Aβ) and somatostatin (SST). Whereas Aβ is best known for its role in Alzheimer disease (AD) as the main constituent of amyloid plaques, SST is intermittently stored in amyloid-form in dense core granules before its regulated release into the synaptic cleft. This review was written to introduce to readers a large body of literature that surrounds these two peptides. After introducing general concepts and recent progress related to our understanding of amyloids and their aggregation, the review focuses separately on the biogenesis and interactions of Aβ and SST, before attempting to assess the likelihood of encounters of the two peptides in the brain, and summarizing key observations linking SST to the pathobiology of AD. While the review focuses on Aβ and SST, it is to be anticipated that crosstalk amongst functional and disease-associated amyloids will emerge as a general theme with much broader significance in the etiology of dementias and other amyloidosis.